The Effect of Scrabble Game on Students' Vocabulary Mastery of Grade Eight at SMP Negeri 12 Pematang Siantar - Daniel J.O Siringoringo; Christian Neni Purba; Asima Rohana Sinaga (CV Putra Publisher, 2023)
The aim of this research is to determine the effect of the reading aloud strategy on the pronunciation abilities of seventh grade students at SMP Negeri 3 Pematangsiantar. In this research, researchers used quantitative research methods with a quasi-experimental design and pre-test, post-test and control designs. The sample for this research consisted of class VIII students at SMP Negeri 12 Pematang Siantar with an average class size of 32 in the 2022–2023 academic year. There are around 288 students in class VIII. By using this technique, the sample that will be used in this research consists of two classes, namely class VIII-8 as the experimental class and class VIII-9 as the control class at SMP Negeri 12 Pematang Siantar. From the results of research conducted at SMP Negeri 12 Pematang Siantar, it was found that there was an influence of the application of the Scrabble game on mastery of mathematics. This can be seen from the students' average score in the test, namely pre-test 54.21 and post-test 76.09, while the researchers' learning results found that the t-test in this study was 2.14. Based on the previously designed hypothesis formulation, the hypothesis is not rejected if tcount is greater than ttable. The meaning of these results is that students who were taught to use the game Scrabble were better than students who did not use the game Scrabble in the classroom treatment process. After carrying out calculations, the researchers found that in this study the t-count was higher than the t-table. Referring to this, we can put forward the following hypothesis. t-count > t-table 5%, namely 2.14 > 1.670. Because the calculated t-value (2.14) is higher than the t-table (1.670) at the 5% significance level for a two-sided test, the null hypothesis is rejected and the alternative hypothesis is accepted. Therefore, the Scrabble Game is very effective as a learning support medium, especially in improving mathematics mastery.